Pengaruh Intervensi Emosi Positif pada Pengobatan Fibromyalgia - Romaito Nasution; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Milna Sari (Pusat Riset dan Inovasi Nasional, 2024)
This meta-analysis investigates the effectiveness of positive emotion-based interventions for patients with fibromyalgia. From a total of 1,247 identified articles, 32 studies (N=2,456 participants) met the inclusion criteria. The results indicate that positive emotion-based interventions significantly reduce pain intensity (g=-0.42, 95% CI [-0.56, -0.28], p<0.001), enhance quality of life (g=0.38, 95% CI [0.25, 0.51], p<0.001), and alleviate depressive symptoms (g=-0.35, 95% CI [-0.48, -0.22], p<0.001). Furthermore, moderator analysis reveals that the duration of the intervention significantly moderates its effects on pain intensity (β=-0.03, p=0.02) and quality of life (β=0.04, p=0.01) in fibromyalgia patients. Among the interventions, mindfulness-based approaches appear most effective in reducing pain (g=-0.51), while cognitive-behavioural therapy shows the greatest efficacy in improving quality of life (g=0.45). These findings extend Fredrickson's (2001)